2023
DOI: 10.1038/s41419-022-05541-x
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0021727 (circ-CD44) promotes ESCC progression by targeting miR-23b-5p to activate the TAB1/NFκB pathway

Abstract: Esophageal squamous cell carcinoma (ESCC) is characterized by high morbidity and mortality. Circular RNAs (circRNAs) play an important role in tumor progression. We discovered an aberrantly expressed circRNA (hsa_circ_0021727) in patients with ESCC. However, the mechanism of action of hsa_circ_0021727 in tumors is unclear. The present study aimed to investigate the biological role of hsa_circ_0021727 and its mechanism in ESCC progression. We screened for the expression of hsa_circ_0021727 in ESCC patients. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The significant transcriptomes associated with ESCC have been widely investigated through high-throughput approaches. For example, known ESCC-related miRNAs include miR-23b-5p, miR-877-3p, and miR-17-92, among others (13)(14)(15)(16). Several published works demonstrated that chemotherapy resistance can be affected by mRNAs like TUG1, ZFX, and NRF2, and miRNAs like miR-130a-3p, miR-125a-5p, and miR-224 (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…The significant transcriptomes associated with ESCC have been widely investigated through high-throughput approaches. For example, known ESCC-related miRNAs include miR-23b-5p, miR-877-3p, and miR-17-92, among others (13)(14)(15)(16). Several published works demonstrated that chemotherapy resistance can be affected by mRNAs like TUG1, ZFX, and NRF2, and miRNAs like miR-130a-3p, miR-125a-5p, and miR-224 (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that circRNAs can participate in the progression of cancer by regulating the NF-κB pathway. 27,28 For example, circWDR37 deficiency inhibits chemotherapy-induced proliferation and metastasis of senescent NPC cells in vitro by inhibiting the NF-κB pathway. 27 We found that circRNA_CDKN1A acts by affecting the NF-κB pathway.…”
Section: Knockdown Of Circrna_cdkn1a Activates the Nf-κb Pathwaymentioning
confidence: 99%
“…Insulin-like growth factor 2 (IGF2BP2) mediates circRUNX1-enhanced FOXP3 expression by acting as a competitive miRNA sponge to inhibit miR-449b-5p activity, thus promoting ESCC cell proliferation and metastasis in vitro and in vivo (53). circCD44 functions as a sponge for miR-23b-5p, activating TGF-β-activated kinase 1/NF-κB signaling and promoting ESCC cell migration, invasion and proliferation (54). circ-0026611 is highly expressed in ESCC cells and exosomes, and exosomal circ-0026611 promotes ESCC lymphangiogenesis by interacting with N-α-acetyltransferase 10 and inhibiting prospero homeobox 1 acetylation and ubiquitination (55).…”
Section: Biological Function and Clinical Significance Of Circrnas In...mentioning
confidence: 99%